Analysis of audit risks specific to public procurements - BENHOUMMANE, Mostafa; TOUAB, Omar (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Public procurement deserves special attention. Every error, fraud, mounting of corruption increases the debt and undermines democracy. Auditors must have a good knowledge of the pitfalls that are present in this area and how to protect themselves from them. The objective of this paper is to identify the various risks inherent in the public procurement procedure in Morocco. We were able to identify three major risks. This is, first of all, to identify the risks related to the internal control system, then, to identify the risks inherent in public procurement. Finally, identify the auditor's risks.